(untitled) (Biological Sciences - PJSIR, 2022)
Samples from Kakul mine and trenches of several phosphorite deposits were studied. These phosphorites oecur in gradational contact with siltstone, dolomite and chert belonging to Abbottabad Cambrian System. Thinly bedded phosphorites occur mostly as pellets and microsphoritc, while the intraclasts and pseudo-oolites are rare. Fluorapatite is abundant in all the samples, while quartz, calcite, dolomite, feldspar, illite and hematite occur in minor phases. These phosphorites are primary marine sediments formed mostly by direct precipitation. Recrystallization is due to intense diagenesis, whereas fcrruginization suggests weathering of phosphatic horizons in Hazara.